Scaffolding Techniques for Young Learners in EFL Classrooms: a Study at Primary Schools in Kecamatan Tempe - Muhammad, Achmad Fajar; Rosmawati, Rosmawati; Fitrah, Muhammad Alfachriza; Nurwidyayanti, Nurwidyayanti; Rizal, A. (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study explores the use of scaffolding techniques in teaching English to young learners in primary schools in Kecamatan Tempe, Kabupaten Wajo. Using qualitative interviews with five teachers and several students from five schools, it identifies commonly used strategies like modeling, guided practice, interactive dialogue, and visual aids. While students responded positively—especially to visual and interactive methods—teachers faced challenges such as large class sizes, mixed proficiency levels, limited resources, and time constraints. The study concludes that scaffolding is effective, but teachers need more training and resources to optimize its use, highlighting implications for teacher development and classroom practice.